2017
DOI: 10.2139/ssrn.3055884
|View full text |Cite
|
Sign up to set email alerts
|

Granularity of Corporate Debt

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 50 publications
(41 reference statements)
1
15
0
Order By: Relevance
“…Moreover, we lack evidence as to whether findings on the dynamics of leverage have implications for a broader range of debt policies, including debt specialization (Colla, Ippolito and Li, 2013), debt maturity (Scherr and Hulburt, 2001) and debt granularity (Choi, Hackbarth and Zechner, 2014). In sum, an investigation of the evolution of entrepreneurial firms' debt policies going back to startup is timely.…”
Section: Introductionmentioning
confidence: 94%
“…Moreover, we lack evidence as to whether findings on the dynamics of leverage have implications for a broader range of debt policies, including debt specialization (Colla, Ippolito and Li, 2013), debt maturity (Scherr and Hulburt, 2001) and debt granularity (Choi, Hackbarth and Zechner, 2014). In sum, an investigation of the evolution of entrepreneurial firms' debt policies going back to startup is timely.…”
Section: Introductionmentioning
confidence: 94%
“…Based on our theory, if the borrower can adjust the debt structure, she would adopt a more diffused debt structure in facing this shock. Choi et al (2014) provides empirical evidence to support this idea. They found that right before the financial crisis financial institutions adopted more diffused term structures.…”
Section: Self-fulfilling Runsmentioning
confidence: 85%
“…But the option is restrictive in the sense that it is open at a certain point of time. We argue that this mechanism is feasible to avoid self-fulfilling runs because there is empirical evidence the granularity of corporate debts has a lot of variation across firms and across time, see Choi et al (2014). It tells that financial firms could issue debt with different maturities for their long-term investment.…”
Section: Self-fulfilling Runsmentioning
confidence: 99%
See 2 more Smart Citations